Bolivia : Selected Issues. (IMF Staff Country Reports; Country Report, 2010)
This paper derives estimates of optimal levels of reserves for Bolivia, focusing on current account shocks as the key balance of payments risk. Bolivia's foreign reserves are adequate, with an optimal level between 29 percent of GDP and 37 percent of GDP. The accumulation of foreign assets stemmed primarily from a persistent current account surplus, in the context of a crawling peg exchange rate regime. Large current account surpluses followed from major terms of trade improvement after the sharp increase in Bolivia's key export commodity prices during the period 2004-08.